Monoclonal gammopathy of undetermined significance and bone health outcomes: a systematic review and exploratory meta-analysis - Veronese, Nicola; Luchini, Claudio; Solmi, Marco; Sergi, Giuseppe; Manzato, Enzo; Stubbs, Brendon (Journal of bone and mineral metabolism, 2018)
Monoclonal gammopathy of undetermined significance (MGUS) is a common condition in the elderly. A number of studies have investigated the relationship between MGUS and bone health outcomes including bone mineral density (BMD), osteoporosis and fractures, but no meta-analysis exists. We conducted a systematic review and exploratory meta-analysis comparing bone health outcomes in patients with MGUS. Two independent authors searched PubMed and Scopus from inception until 19 October 2016. A meta-analysis of cross-sectional and longitudinal studies investigating fractures and BMD was conducted. Standardised mean differences (SMD) ± 95% confidence intervals (CIs) were calculated for BMD, and risk ratios (RRs) were calculated for prevalent and incident fractures. Of 174 initial hits, 10 studies of moderate methodological quality were eligible, including 8711 individuals with MGUS vs. 52,865 controls. Compared to controls, subjects with MGUS showed significantly lower values for radial cortical volumetric BMD (1 study; SMD = −5.45, 95% CI: −7.24 to −3.66), but not at the lumbar spine, femoral neck or hip. The incidence of fractures was higher in people with MGUS ( n = 7466) vs. controls ( n = 52,304) (RR = 1.36, 95% CI 1.28–1.44, I 2 = 0%) over a median of 12.5-year follow-up. The incidence of vertebral fractures was particularly elevated (RR = 2.50, 95% CI 1.53–4.06) although limited to two studies. In conclusion, although with limitations, our preliminary meta-analysis suggests that patients with MGUS are at higher risk of fractures despite evidence for differences in BMD being equivocal. Future longitudinal research is required to confirm our findings and determine if fracture prevention interventions are warranted in people with MGUS.